De Novo Subgaleal Abscess. (1992) - Schaefer, JP; Clein, LJ; Conly, JM
Abstract : The authors report a case of spontaneous subgaleal abscess formation in a 62-year-old woman without antecedent trauma or injury. She presented with occipital scalp pain and swelling which rapidly became generalized two days following recovery from an upper respiratory infection. Diagnosis was based on radiological examination and aspiration of the subgaleal space, which yielded a purulent exudate with a pure growth of Streptococcus pyogenes. Initial management with incision, drainage and parenteral antimicrobial therapy was not successful. Operative exploration of the subgaleal space revealed extensive necrosis of the galea aponeurotica, and bone curettings revealed microscopic evidence compatible with osteomyelitis. Management with debridement and excision of all necrotic tissue plus prolonged parenteral antimicrobials was successful. Subgaleal abscess formation without an overlying wound or previous trauma has not been reported previously.